Recent Patents in Dendrimers for Nanomedicine: Evolution 2014 - Shcharbin, Dzmitry; Shcharbina, Natallia; Bryszewska, Maria (Recent Patents on Nanomedicine, 2014)
Application of nanotechnology in medicine has resulted in the appearance of new supramolecular systems, complexes and composites. Among these, dendrimers are represented, which are globular in shape with a topological structure formed by monomeric subunit branches on all sides emerging from the central nucleus. This article gives a short patent overview on their possible applications in medicine. Dendrimers can act as contrast agents, drug and gene delivery carriers, drugs treating amyloidosis (including Alzheimer’s disease), antibacterial and antiviral agents, antioxidants, vaccines, immunostimulants (adjuvants), tissue coatings, and dental and medical polymer composites.
Keywords: gene therapy